Mitochondrial haplogroup H1 is protective for ischemic stroke in Portuguese patients - Rosa, A. (2011)
The genetic contribution to stroke is well established but it has proven difficult to identify the genes and the disease-associated alleles mediating this effect, possibly because only nuclear genes have been intensely investigated so far. Mitochondrial DNA (mtDNA) has been implicated in several disorders having stroke as one of its clinical manifestations. The aim of this case-control study was to assess the contribution of mtDNA polymorphisms and haplogroups to ischemic stroke risk.